Self-Narrative Vizualization in Contemporary Travel Text - Юферева, Олена Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The research of photo narrative is currently increasing, the prime evidence is observed in the effective scholars of the interactions between photography and an autobiography. The main questions of this paper are by what means of photo narrative travel bloggers construct the self-image and an imaginary space image as well, in what ways we could explicate the meaning of the visual self-narration in Internet travel writing. The article reveals the essential concepts of study the problem, such as “autoportraitistic pact”, “transmedial narrative”, “phototextuality”. The author stresses that there is no any argumentative research of the correspondence between literature and photography in humanitarian discourse of Ukraine.From an overall perspective the key information that stands out from the analysis of travel blogs is that photography appeals to emotional and symbolic semantics. Taking this argument further this point should be supplemented with the factor of theatralization of bloggers’ behavior, which reflects the autoportraits. The shoots of traveler from behind in front of the open space are the cliché that involves the collective patterns of this practice that are associated with rhe romantic image of a wanderer. As so the portraits can be seen as part of broader culture tradition. The author provides the examples of some variants of this picture composition. More specifically, there are some photos with diegetic function in a travelogue by Orest Zub.The narrative analysis of visual stories turns out that they tend to a distant narrative position. The gaps between the visual and verbal texts indicates the peculiarities of focalization and the tension between the axiological positions of the narrator and the author of the blog.Finally, the stereotypes of visual stylistics, similarity of selfrepresentation due to utopian image of travelling as a practice that releases a person from prosaic everydayness.